التأمين في ضوء السنة النبوية - العواد، ريم عبدالله صالح (جامعة المدينة العالمية, 2023)
التأمين هو وسيلة لمواجهة المخاطر التي يتعرض لها الإنسان في كيانه وأمواله أثناء فترة حياته في سبيل التخفيف من وطأتها، وهي قضية من قضايا العصر ذات الفائدة الاجتماعية والاقتصادية للأفراد، وسوف نعرض هنا المراد به، وبتاريخ نشأته، وأنواعه، والفرق بينهما، وحكم كل نوع، والقول الراجح في ذلك، من خلال الاطلاع على كتب السنة النبوية، وكتب الفقه الإسلامي الحديثة وربطها ببعضها، ومحاولة التوفيق بينهما للوصول إلى المعنى الحقيقي للتأمين وأنواعه، وثم تقسيم البحث إلى مقدمة وفصلين ويضم كل فصل ثلاثة مباحث والخاتمة والنتائج التي تم الوصول لها من: المراد بالتأمين عامة وبأنواعه خاصة وحكمها، والوصول في النهاية إلى القول الراجح فيهما، ثم فهارس المصادر. Insurance is a way to face the risks that a person is exposed to in his being and his money during his life period in order to mitigate their impact, and it is one of the issues of the era that has social and economic benefit for individuals. We will present here what is meant by it, the date of its inception, its types, the difference between them, and the ruling on each type. the most correct way to say this is by looking at the books of the Sunnah of the Prophet and the books of modern Islamic jurisprudence and linking them to each other and trying to reconcile them to reach the true meaning of insurance and its types, and then dividing the research into an introduction and two chapters, and each chapter includes three topics and the conclusion and the results that have been reached from insurance in general and its types in particular and its ruling, and finally arriving at the most correct opinion in them, then the source indexes.
Keywords: السنة النبوية -- الفقه الإسلامي -- التأمين التجاري